Treatability of cheese whey for single-cell protein production in nonsterile systems: Part I. Optimal condition for lactic acid fermentation using a microaerobic sequencing batch reactor (microaerobic SBR) with immobilized Lactobacillus plantarum TISTR 2265 and microbial communities - Monkoondee S. (2017)
© 2016 Taylor & Francis. ABSTRACT: Cheese whey contains a high organic content and causes serious problems if it is released into the environment when untreated. This study aimed to investigate the optimum condition of lactic acid production using the microaerobic sequencing batch reactor (microaerobic SBR) in a nonsterile system. The high production of lactic acid was achieved by immobilized Lactobacillus plantarum TISTR 2265 to generate an acidic pH condition below 4.5 and then to support single-cell protein (SCP) production in the second aerobic sequencing batch reactor (aerobic SBR). A hydraulic retention time (HRT) of 4 days and a whey concentration of 80% feeding gave a high lactic acid yield of 12.58 g/L, chemical oxygen demand (COD) removal of 62.38%, and lactose utilization of 61.54%. The microbial communities in the nonsterile system were dominated by members of lactic acid bacteria, and it was shown that the inoculum remained in the system up to 330 days.